Efficacy and Safety of Direct-Acting Antivirals in Kidney Transplantation From HCV-Viremic Donors to Negative Recipients: A Meta-Analysis - Feng, Zepei; Zhang, Jinwei; Tan, Weilong; Wang, Chunhui; Chen, Qiong; Shen, Chao; Fan, Haozhi; Zhang, Yun; Huang, Peng; Yue, Ming (Frontiers in Medicine, 2022)
Background: With the development of direct-acting antiviral agents (DAAs), The kidneys transplantation from hepatitis C virus (HCV)-viremic donors into HCV negative recipients has grown. The objective of this comprehensive analysis was to evaluate the efficacy and safety of DAAs in kidney transplantation from HCV-viremic donors to negative recipients. Methods: Multiple databases were searched for a systematic and comprehensive up to February 2022. The primary outcomes included the percentage of sustained virological response at week 12 after the end of treatment (SVR12), adverse events (AEs; any grade) and severe adverse events (SAEs) as the endpoints. Publication bias was examined by using funnel plots and Egger’s test. Results: Sixteen studies with 454 subjects were included in the study and the pooled estimate of SVR12, AEs and SAEs rates were 100.0% (95%CI: 99.2-100.0), 1.9%(95%CI: 0.0–4.9) and 0.0% (95%CI: 0.0–1.5). Subgroup analysis showed that pooled SVR12 rates were 100.0% (95%CI: 99.6-100.0) for genotype (GT)1a and 96.3% (95%CI: 83.3-100.0) for GT2; 100.0% (95%CI: 98.9-100.0) for DAAs treatments, 100.0% (95%CI: 98.2–100.0) for prophylaxis subgroup. Egger’s tests showed that no publication bias was found in this study. Conclusion: This comprehensive analysis showed the high efficacy and safety of DAAs in kidney transplantation from HCV-viremic donors to HCV-negative recipients.